An interval type-2 fuzzy logic PSS with the optimal H∞ tracking control for multi-machine power system. (2016) - Meziane, Khaddouj Ben; Boumhidi, Ismail
In this paper, the interval type-2 fuzzy logic controller (IT2FLC) as a power system stabiliser (PSS) combined with the optimal H∞ tracking control is proposed in this study. The multi-machine power system is considered for evaluation and implementation of the robust proposed controllers. The type-2 fuzzy logic based on interval value sets is capable for modelling the uncertainty and imprecision and to overcome the drawbacks of the conventional PSS. The input signals to the IT2FLC are considered as speed deviation and acceleration. The optimal H&infin tracking control guarantees the convergence of the errors to the neighbourhood of zero. The objective of the proposed method is to enhance the stability and the dynamic response of the multi-machine power system in different operating conditions. The performance with (IT2FL-PSS and H∞) is compared to the performance of the power system with (IT1FL-PSS and H∞) and with conventional PSS. In order to test the effectiveness of the proposed method, the simulation results show the damping of the oscillations of the angle and angular speed with reduced overshoots and quick settling time.